Impact of superconducting fault current limiters on Delayed Current Zeros in industrial power systems. (February 2023) - Silva, R.F.; Mafra, G.R.F.Q.; Sotelo, G.G.; Fortes, M.Z.; Trillaud, F.; Guillen, D.
Abstract: Electric power systems may exhibit fault currents with high asymmetry when generators are close to large motors and loads. In this condition and depending on the fault inception instants, the fault current waveforms may present Delayed Current Zeros (DCZ). During transient studies, in some cases, breakers do not see the current zero-crossing for several cycles. Indeed, if the breaker opens just after a transient when the current has not reached steady-state and may be offset by a slow exponentially decaying DC component, then, the breaker will fail to open as the current will not cross zero within the interruption time. Here, the main concern associated with DCZ is however related to the interruption of the circuit breakers on a current wave crossing zero. At this moment, the interruption is accompanied of an electrical arc having the potential to damage equipment. Resistive superconducting fault current limiters (r-SFCL) are a known solution to reduce the magnitude of short-circuit current in electrical systems. It is a versatile technology that can tackle both fault and stability issues in aging and modern power grids alike. As a side benefit, it may also address the DCZ problem. The present work aims at investigating the impact that an r-SFCL may have on DCZ and, in particular, its ability to eliminate this issue altogether. To that end, a r-SFCL based on an existing design was modeled using the consolidated thermal–electrical analogy. This approach has proven to be fairly accurate to model the transient behavior of the superconducting device. Here, the case study simulates a solid short-circuit at the terminal of a generator in a specific bus, simulating an industrial power system, that includes a circuit breaker, a motor load, and a r-SFCL. The electromagnetic transient computations were carried out considering load and no-load conditions with and without the r-SFCL. Eight scenarios were considered, showing that r-SFCLs can actually address DCZ in addition to limit the fault level. Highlights: Delayed Current Zeros in Industrial Power Systems. Superconducting Fault Current Limiters applications. r-SFCL applied to Power System Protection.